2003
DOI: 10.1002/ejoc.200300257
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Terminating Radical Oxygenations: Probing of the Scope of the Concept by Use of Various Organic O‐Centered Radicals

Abstract: Addition of various organic O‐centered radicals XO• {i.e. (alkoxycarbonyl)oxyl radicals, ROC(O)O•, [(alkoxycarbonyl)acyl]oxyl radicals, ROC(O)C(O)O•, (carbamoyl)oxyl radicals, R2NC(O)O•, alkoxyl radicals, RO•, and nitroxyl radicals, R2NO•} to alkynes initiates an oxidative radical cyclization cascade, which is terminated by release of a C‐ or N‐centered radical X•. This finding clearly highlights the generality of the recently discovered concept of self‐terminating radical oxygenations, through which C≡C tripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…[5] We have meanwhile demonstrated that this type of self-termination is a very general concept in radical chemistry, and many different inorganic, organic, uncharged, and even charged O-centred radicals can act, similar to NO • 3 , as O-atom donors in their reactions with alkynes. [6] Both experimental [4] and theoretical investigations [7] have revealed that the 1,5-HAT is the rate-limiting step in this sequence, whereas the diastereoselectivity is likely determined in the subsequent 5-exo cyclization of radical intermediate 4. Besides the size and stereochemistry (cis or trans) of the fused cycloalkane ring, it was found that both absence or presence of the heteroatom (X = O) as well as the nature of the substituent R influenced the diastereoselectivity of this cyclization step.…”
Section: Introductionmentioning
confidence: 99%
“…[5] We have meanwhile demonstrated that this type of self-termination is a very general concept in radical chemistry, and many different inorganic, organic, uncharged, and even charged O-centred radicals can act, similar to NO • 3 , as O-atom donors in their reactions with alkynes. [6] Both experimental [4] and theoretical investigations [7] have revealed that the 1,5-HAT is the rate-limiting step in this sequence, whereas the diastereoselectivity is likely determined in the subsequent 5-exo cyclization of radical intermediate 4. Besides the size and stereochemistry (cis or trans) of the fused cycloalkane ring, it was found that both absence or presence of the heteroatom (X = O) as well as the nature of the substituent R influenced the diastereoselectivity of this cyclization step.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of 9a was again chosen as model system, and ROC(O)O • , ROC(O)C(O)O • , R 2 NC(O)O • and RO • were generated through photolysis of the corresponding precursors 3 and 5 (Scheme 1.5 and 1.6) in the presence of 9a . In all cases, formation of the bicyclic ketones 10a/11 was observed ( Table 1 , entries 8–16) [ 74 ]. As with RC(O)O • , the outcome was significantly dependent on the concentration of the “radical scavenger” 9a , and by using a roughly three-fold excess of 9a , generally good to excellent yields of 10a/11 were obtained [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…0.3 eq. ), and the reaction was carried out under ultrasound treatment in the absence of light ( Table 1 , entries 17 and 18) [ 74 , 77 , 78 ]. It was important to use nitroxyl radicals with at least one sp 2 center adjacent to nitrogen, since steric hindrance around the radical site significantly influenced the success of the anyway difficult reaction.…”
Section: Resultsmentioning
confidence: 99%
“…All major classes of inorganic and organic O-centered radicals XO . , for example, SO 4 35 and RO . (X ¼ R), 36 have been shown to promote oxidation of, for example, cycloalkyne 52 to give the bicyclic ketones 53 and 54.…”
Section: Cascade Reactions Initiated By Addition Of C-centered Radicamentioning
confidence: 99%